Quantitative Analysis of Favipiravir by HPLC: Development and Validation - Moammal Qurt; Rania Eshtayyeh; Hani Naseef; Abdullah Rabba; Abdallah Damin Abukhalil; Numan Malkieh; Maher Kharouf (International Journal of Analytical Chemistry)
Favipiravir is a broad-spectrum oral antiviral agent and has been approved for the treatment of COVID-19 infection cases. It inhibits a protein known as RNA polymerase, which transcribes and replicates the viral RNA genome, causing the spread of the infection. The current study aimed to develop and validate a new analytical method utilizing HPLC in accordance with international requirements (ICH and FDA). The chromatographic conditions used to achieve good resolution and reproducibility were a mixture of acetonitrile and 0.1% phosphoric acid buffer in the ratio of 60 : 40 v/v as the mobile phase. The flow rate was 1.0 mL/min, the wavelength (λ) was determined at 250 nm, and a retention time was approximately 3 minutes for favipiravir. The HPLC analysis was performed on the Dionex 300 system equipped with a Phenomenex C8 (250 cm 4.6 mm) 5 μm column. The total runtime was 6.0 min. The findings indicated that the method had been validated satisfactorily. Across the concentration range of 0.10–0.75 mg/ml, the calibration curve revealed a linear relationship. The accuracy of the current method was to be 99.2%. The limit of detection (LOD) and limit of quantification (LOQ) were 0.004 and 0.013 ppm, respectively. The standard and sample solution repeatability tests revealed that the procedure was precise and within acceptable ranges. The RSD% for the determination of precision was <2%. The results for robustness and solution stability were within acceptable limits. Finally, the new method provided an excellent result for all analytical method validation parameters and met the acceptance criteria. In addition, the new approach has a short run time and a retention time of around 4 minutes.